2019
DOI: 10.1038/s41598-019-42842-2
|View full text |Cite
|
Sign up to set email alerts
|

New Approach in Ulcer Prevention and Wound Healing Treatment using Doxycycline and Amoxicillin/LDH Nanocomposites

Abstract: Doxycycline (DOX) and amoxicillin (AMOX) are important Broad-spectrum antibiotics used in treating multiple human and animal diseases. For the sake of exploring novel medical applications, both antibiotics were loaded into magnesium aluminium layer double hydroxide (Mg-Al)/LDH nanocomposite through the co-precipitation method. The synthesized materials were characterized by XRD, FT-IR, particle size analysis, FESEM and HRTEM. Acute toxicological studies were conducted using median lethal dose LD 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 73 publications
0
20
0
1
Order By: Relevance
“…The study conducted by Fatma I. Abo El-Ela et al showed appropriate treatment of diabetes foot infection by amoxicillin and doxycycline help to prevent bacterial growth and ulcers that heal the wounds within a short period [ 18 ]. According to the study done in China by Chu et al, for moderate/severe infection, the healing rate was rapid in patients given appropriate antibiotic therapy [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Fatma I. Abo El-Ela et al showed appropriate treatment of diabetes foot infection by amoxicillin and doxycycline help to prevent bacterial growth and ulcers that heal the wounds within a short period [ 18 ]. According to the study done in China by Chu et al, for moderate/severe infection, the healing rate was rapid in patients given appropriate antibiotic therapy [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…2, spectrum b and inset (i) show the appearance of important bands of cefotax in the spectra of the Zn-Al LDH/cefotax composite as follows: stretching of O-H groups appeared at 3456 cm À1 , N-H stretching is shown around 1569 cm À1 , C]O stretching vibration of (COO) 2À at 1852.76 cm À1 , the peaks at 1623, 1494.10, 1367.96, 1032, 772, and 610 cm À1 are due to the presence of C]O of an amide group, N-H, C]O, C-N, C-O, CH 2 , and C-S groups, respectively. 50 Two clear pieces of evidence demonstrated the successful loading of cefotax on the Zn-Al LDH host: the appearance of cefotax bands and the difference between the two spectra, which was obvious and manifested in peaks shiing toward high wavenumbers, including the -OH group peak at 3454 cm À1 shied to 3456.87 cm À1 , the bending vibration of OH peak at 1620 cm À1 shied to 1623.04 cm À1 denoting the promotion of hydrogen bonding interactions between Zn-Al LDH and cefotax, 24 C]O at 1365.67 cm À1 shied to 1367.96 cm À1 , and the M-O bond stretching at 692 shied to 610 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in zeta potential value reected that cefotax was extensively obtained as a successful nanocomposite formulation, not only through hydrogen bonding as referred by FTIR but also via electrostatic interaction. 24,66 3.1.5. BET and TGA-DTA analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations